Low Proficiency Students’ Attitudes toward English Writing, Dialogue Journal Writing and their Willingness to Write in English - Madeng, Mareekee; Palanukulwong, Thanyapa (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 3 (2562): Academic Services Journal, Prince of Songkla University, 2019)
This study aimed to examine the students’ attitudes toward English writing, the use of dialogue journals and examine whether students’ willingness to write increased after the use of dialogue journals. Twenty-nine Mattayom Suksa 4 (grade 10) students in an Islamic private school participated in this 14-week study. Each was required to write a journal once a week. The dialogue journal was responded by a peer with a comparable level of English proficiency. Journal entries and three sets of questionnaires were used as instrument for data collection. The students’ responses to questionnaire toward English writing, the use of dialogue journal writing (DJW) and their willingness to write were quantitatively analyzed. The results revealed that students had positive attitudes toward writing in English, the use of DJW, and they were more willing to write after the implementation of dialogue journal writing. Keywords: low proficiency students, English writing, dialogue journal writing, willingness to write